Violation of Legally Binding Peace Agreements Legal Implications and Resolution Solutions - Hans Karyose; Muhammad Ansari; Ade Saptomo (Journal Equity of Law and Governance, 2025)
Disputes arise between two or more parties when one party feels dissatisfied or harmed. Fundamentally, disputing parties are granted the freedom to determine their preferred dispute resolution mechanisms. According to Laura Nader and Harry F. Todd, disputes evolve through three stages: (1) Pre-conflict, characterized by underlying dissatisfaction; (2) Conflict, when the parties become aware of the dissatisfaction; and (3) Dispute, where the conflict is openly expressed or involves a third party.  Legally binding peace agreements are crucial instruments for resolving disputes across various legal domains, including civil, criminal, and administrative law. However, in practice, there are frequent instances where one party fails to uphold the terms of a court-ratified peace agreement. This paper examines the legal aspects of violations of legally binding peace agreements, their implications, and the potential solutions to ensure the sustainable implementation of such agreements.